2017
DOI: 10.1371/journal.pone.0172888
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity and in situ detection of eukaryotes in anaerobic sludge digesters

Abstract: Eukaryotic communities in aerobic wastewater treatment processes are well characterized, but little is known about them in anaerobic processes. In this study, abundance, diversity and morphology of eukaryotes in anaerobic sludge digesters were investigated by quantitative real-time PCR (qPCR), 18S rRNA gene clone library construction and catalyzed reporter deposition-fluorescence in situ hybridization (CARD-FISH). Samples were taken from four different anaerobic sludge digesters in Japan. Results of qPCR of rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…Generally considered and regardless of the bioreactor, Rotifera and Phragmoplastophyta were the most representative phyla. In contrast to Matsubayashi et al, we found that Rotifera phylum is also abundant in anaerobic activated samples. Eukaryal phylotypes were mainly clustered to Fungi (42.2%), Animalia (28.8%), Protista (13.3%), and finally Plantae (8.9%).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Generally considered and regardless of the bioreactor, Rotifera and Phragmoplastophyta were the most representative phyla. In contrast to Matsubayashi et al, we found that Rotifera phylum is also abundant in anaerobic activated samples. Eukaryal phylotypes were mainly clustered to Fungi (42.2%), Animalia (28.8%), Protista (13.3%), and finally Plantae (8.9%).…”
Section: Resultscontrasting
confidence: 99%
“…A total of 38 different eukaryal OTUs were detected in the samples of the biomass from MC, AD, and MD (Figure S1C and Figure c). The role of eukaryotes during aerobic treatment processes have been associated with an excess of sludge production and performance and predation of bacteria but few studies have investigated the diversity of eukaryotes in anaerobic digestion . Generally considered and regardless of the bioreactor, Rotifera and Phragmoplastophyta were the most representative phyla.…”
Section: Resultsmentioning
confidence: 99%
“…If it is possible to publish new species from the computer just on the basis of a DNA sequence, not only knowledge of the morphology, anatomy, chemistry, physiology, life history strategies and ecology of fungi would lose value, but researchers interested in organismal mycology might be discouraged to intensely study and characterise species right from the start, eroding the foundation on which fungal systematics is built. If all the ‘dark matter’ of the cryptic basal lineages of fungi ( Grossart et al 2016 ) would be formally named based on sequence data, this would probably also discourage the laborious search for these organisms by FISH and other microscopy techniques ( Jones et al 2011 , Lazarus & James 2015 , Lepère et al 2016 , Matsubayashi et al 2017 ). Another problematic issue is that if sequence data were accepted as type, specimens might be seen as obsolete and only cost-prohibitive museum objects, as they are more difficult to store, curate and preserve than sequence data.…”
Section: Ten Reasonsmentioning
confidence: 99%
“…The biogas microbiome does not only comprise bacteria and archaea but also viruses/phages [7] as well as eukaryotes including fungi and protists (mainly protozoa) which are less investigated [8][9][10]. While it is assumed that the functional characteristics of pro-and eukaryotes are closely related to each other in a cooperative way [11], viruses/phages are suspected to have regulatory effects on the microbial cell turnover [7,12].…”
Section: Introductionmentioning
confidence: 99%